2017
DOI: 10.46792/fuoyejet.v2i1.51
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Forced Convective Heat Transfer and Fluid Flow in a Finned Cylindrical Annulus

Abstract: The purpose of this paper is to numerically investigate the effects of some geometric parameters and flow variables on heat transfer augmentation in annuli with equi-spaced internal longitudinal fins along the external walls. A fully developed flow and a constant thermal boundary condition of uniform heat flux at the walls of the pipe were assumed. Continuity, momentum and energy transport equations were adopted for the solutions of the problem. A Q-BASIC code was written based on the finite difference scheme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…[5] conducted research on free convection inside square cavity featuring isothermal vertical walls, adiabatic horizontal walls, and a rectangular hot cylinder positioned at various horizontal locations, they concluded that the Rayleigh number and location of rectangular cylinder both impact the properties of flow and heat transport. Adegun et al [6] scrutinized the phenomenon of laminar forced convection heat transmission and flow occurring within a shaped cylindrical annulus. A new study of inquiries gives a wide summary of the flow domain and heat transport within various types of cylinders in different geometries of enclosures [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[5] conducted research on free convection inside square cavity featuring isothermal vertical walls, adiabatic horizontal walls, and a rectangular hot cylinder positioned at various horizontal locations, they concluded that the Rayleigh number and location of rectangular cylinder both impact the properties of flow and heat transport. Adegun et al [6] scrutinized the phenomenon of laminar forced convection heat transmission and flow occurring within a shaped cylindrical annulus. A new study of inquiries gives a wide summary of the flow domain and heat transport within various types of cylinders in different geometries of enclosures [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, Nazari et al [32], in their investigation of the flow of a non-Newtonian nanofluid, observed that the thermal profiles in the enclosure depend on both the Darcy number and nanofluid volume fraction. Using an EC, several investigations are available on heat transfer under the influence of natural convection and forced convection [33][34][35][36]. The literature shows that geometric ratio and Rayleigh number influence heat transfer augmentation significantly.…”
Section: Introductionmentioning
confidence: 99%
“…nergy utilization in systems such as power generation, combustion, refrigeration and air conditioning usually leads to generation of surplus thermal energy which must be removed as waste heat for the optimal performance of the system. Forced convective fluid flow and heat transfer arises in a range of engineering problems particularly when viscous fluids are heated and the heat transfer involved is low (Adegun et al, 2017). One of the ways to achieve waste heat removal from these systems is to dissipate the heat rejected to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%